2016
DOI: 10.1242/dev.137372
|View full text |Cite
|
Sign up to set email alerts
|

Of sex and determination: marking 25 years of Randy, the sex-reversed mouse

Abstract: On Thursday 9 May 1991, the world awoke to front-page news of a breakthrough in biological research. From Washington to Wollongong, newspapers, radio and TV were abuzz with the story of a transgenic mouse in London called Randy. Why was this mouse so special? The mouse in question was a chromosomal female (XX) made male by the presence of a transgene containing the Y chromosome gene Sry. This sex-reversal provided clear experimental proof that Sry was the elusive mammalian sex-determining gene. Twenty-five yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…In the early 1990s, SRY (‘sex-determining region Y protein’) was identified as the main Y-chromosomal driver for testis development, supported by the generation of ‘Randy’, an XX mouse that developed testes and a male phenotype owing to the presence of a Sry transgene [1]. SRY is also crucially important in human testis determination, although only approximately 5% of individuals with testicular dysgenesis have disruption of this transcription factor.…”
Section: Human Sex Developmentmentioning
confidence: 99%
“…In the early 1990s, SRY (‘sex-determining region Y protein’) was identified as the main Y-chromosomal driver for testis development, supported by the generation of ‘Randy’, an XX mouse that developed testes and a male phenotype owing to the presence of a Sry transgene [1]. SRY is also crucially important in human testis determination, although only approximately 5% of individuals with testicular dysgenesis have disruption of this transcription factor.…”
Section: Human Sex Developmentmentioning
confidence: 99%
“…Studies in transgenic mice and humans with SRY deletions and translocations have suggested that SRY is the primary Y-chromosomal testis-determining gene in humans, but direct evidence is limited (Bashamboo et al, 2017; Hanley et al, 2000; Koopman et al, 2016). SRY is thought to be transiently up-regulated in the 46,XY bipotential gonad at around 42 dpc, leading to downstream expression of testis development pathways (Hanley et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…The role of SRY as the primary testis-determining gene has been known for 25 years, following transgenic mouse studies as well as the discovery of duplication of SRY in individuals with 46,XX testicular disorders of sex development (DSD) or disruption of SRY in 46,XY testicular dysgenesis (Bashamboo et al, 2017; Koopman et al, 2016; Svingen & Koopman, 2013). SRY is believed to undergo a transient wave of expression in the developing testis that regulates transcription of downstream factors such as SOX9 and initiates testis development pathways (Hiramatsu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human sex development is dictated by the inheritance of either an X or Y chromosome from the father to offspring. The male sex determination step starts with the expression of a Y-chromosome-encoded transcription factor SRY (sex-determining region Y) in the bipotential gonad, initiating a cascade of molecular and cellular events leading to testicular organogenesis [ 1 ]. In the absence of the Y chromosome, female-specific pathways are initiated for proper ovarian development [ 2 ].…”
Section: Introductionmentioning
confidence: 99%